Endorsement of universal health coverage financial principles in Burkina Faso. (February 2016) - Agier, Isabelle; Ly, Antarou; Kadio, Kadidiatou; Kouanda, Seni; Ridde, Valéry
Abstract: In West Africa, health system funding rarely involves cross-subsidization among population segments. In some countries, a few community-based or professional health insurance programs are present, but coverage is very low. The financial principles underlying universal health coverage (UHC) sustainability and solidarity are threefold: 1) anticipation of potential health risks; 2) risk sharing and; 3) socio-economic status solidarity . In Burkina Faso, where decision-makers are favorable to national health insurance, we measured endorsement of these principles and discerned which management configurations would achieve the greatest adherence. We used a sequential exploratory design. In a qualitative step (9 interviews, 12 focus groups), we adapted an instrument proposed by Goudge et al. (2012) to the local context and addressed desirability bias. Then, in a quantitative step (1255 respondents from the general population), we measured endorsement. Thematic analysis (qualitative) and logistic regressions (quantitative) were used. High levels of endorsement were found for each principle. Actual practices showed that anticipation and risk sharing were not only intentions. Preferences were given to solidarity between socio-economic status (SES) levels and progressivity. Although respondents seemed to prefer the national level for implementation, their current solidarity practices were mainly focused on close family. Thus, contribution levels should be set so that the entire family benefits from healthcare. Some critical conditions must be met to make UHC financial principles a reality through health insurance in Burkina Faso: trust, fair and mandatory contributions, and education. Highlights: Anticipation by precautionary savings is an established practice, as are loans and donations. Risk sharing for health expenses, is widely accepted; social bond strength is a key factor. Solidarity among SES levels is highly endorsed, with preference for progressivity. National-level UHC implementation is accepted and aligned with experts' recommendations. Sound and trustworthy UHC funds management will be critical to achieving adherence.